A classification of several Yamato-75 chondrites (V) - Matsumoto, Yukio; Kojima, Hideyasu; Jyo, Nobuyuki (1984)
P(論文) Electron microprobe studies have been made of olivines and pyroxenes in 19 Yamato-75 chondrites which were collected from the Yamato Mountains area, East Antarctica by the 16th Japanese Antarctic Research Expedition (1974-1976) (JARE-16). These chondrites are classified on the basis of textural characteristics of chondrules, matrix, plagioclase and igneous glass, and on the compositions of olivines and orthopyroxenes. As a result, the chondrites are tentatively classified as follows : type H3 (Yamato-75029), type H4 (Yamato-75096,-75269), type H4-5 (Yamato-75291), type H5-4 (Yamato-75262), type H5 (Yamato-75012,-75259), type H5-6 (Yamato-75267), type H6 (Yamato-75100,-75277,-75304), type L4 (Yamato-75019), type L4-5 (Yamato-75297), type L5 (Yamato-75017,-75270,-75288,-75289), type L6 (Yamato-75071), type LL6 (Yamato-75258). departmental bulletin paper